Cooperativismo agropecuário e desenvolvimento local : a experiência da Coopercinco - Perim, Mary Lúcia Silva (2018)
From its emergence to the present day, cooperativism has faced different moments, crises, been confronted, restructured and established as a movement that, in itself, is able to be, even operating in a capitalist environment, an instrument capable of mitigating economic traumas and social problems experienced by individuals as a result of capitalism and thus, continues to be fruitful in cooperatives of various branches and activities, generating benefits provided through cooperation that are manifested in many parts of the world. In Brazil, the benefits generated by cooperatives and cooperatives can be seen more broadly, especially in the South and Southeast regions, considering that they have been historically colonized by people of European origin, originating from the cradle of the cooperative movement. cooperative way of life, being strong propagators of the movement. The other Brazilian regions also received cooperativism, however, at a slower pace. In the North Region, considering the form of territorial occupation and economic activity based on vegetal and mineral extractivism, the cooperative movement was essentially developed through extractivist cooperatives, mainly focused on the exploitation of rubber. In Roraima, there are few data on the emergence of cooperativism, but there is a record in the state's commercial junta that shows that in 1979 there was an agricultural cooperative in the south of the state. In the 1980s and 1990s, Roraima cooperativism gained strength, especially in the municipalities of the South of the State, especially the Municipality of Caroebe, due to the large banana production and incentives from the state government to that locality. The research presented here has the general objective of analyzing the actions taken by the management of the Coopercinco Cooperativa Agropecuária dos Five Polos, which arose from the need of the small family farmers of the New Amazon Settlement Project (PANA) to commercialize their production. Thus, the local actors, formally organized through Coopercinco, sought through the activities they already carried out in their day to day, to explore in a systematized way, to expand their productive capacities, to add value to their products, using the available productive factors used in their properties, in order to achieve better living conditions. It was concluded that it is through Coopercinco's activity that the associated producers have the opportunity to access and participate in sales to institutional markets, specifically, the National School Feeding Program (PNAE) and the Food Acquisition Program (PAA). fact gave them autonomy, since they are no longer forced to sell their products to the middlemen. Coopercinco gave the possibility of agroindustrialization of cooperative products, even at a small scale, increasing its value added, causing a significant increase in family financial gain and expansion of business opportunities. With the activities of agro-industrialization, Coopercicnco has been contributing to the employment and diffusion of new technologies, generating collective learning, which carry in itself great possibilities of generating positive impacts in the near future. In this context, it was evidenced that local actors are the protagonists of its own development process, and even faced difficulties in the aspect of management and market action, Coopercinco seeks to meet the needs of its members regarding the representativeness of their interests. Therefore, the logic of cooperativism can be considered as a viable competitive strategy and a driver of local development.